Analisis Potensi Pendapatan Pajak Daerah dalam Upaya Peningkatan Pendapatan Asli Daerah Kalimantan Selatan - Noorhidayanti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The purpose of this research is to know the description of the tax area now and to find out how the tax potential of Regions in an attempt to increase Revenue of theoriginal South Kalimantan.The object of this research is in the province of South Kalimantan. The type of this research is quantitative, i.e., data-shaped figures or numbers. The data used in this research is secondary. The data in this study using the method of estimation is to figureout how significant the tax potential of regions of the province of South Kalimantan belongs to the Original income area.The results of this research the potential tax areas of the province in the form of motor vehicle Taxation (PKB), the motor vehicle fuel tax (PBBKB), Customs Tax behindthe name of motor vehicle Tax (PBBNKB), surface water (PAP) and taxes of cigarettes owned South Kalimantan very high against the original Revenue areas.